2022
DOI: 10.1186/s13059-022-02681-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying common transcriptome signatures of cancer by interpreting deep learning models

Abstract: Background Cancer is a set of diseases characterized by unchecked cell proliferation and invasion of surrounding tissues. The many genes that have been genetically associated with cancer or shown to directly contribute to oncogenesis vary widely between tumor types, but common gene signatures that relate to core cancer pathways have also been identified. It is not clear, however, whether there exist additional sets of genes or transcriptomic features that are less well known in cancer biology b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 95 publications
1
4
0
Order By: Relevance
“…Then scanpy was utilized to cluster several cell groups from scRNA-seq datasets of breast cancer tissues. Our results show similar clustering performance compared to that when using real scRNA-seq datasets [29].…”
Section: Methodssupporting
confidence: 68%
“…Then scanpy was utilized to cluster several cell groups from scRNA-seq datasets of breast cancer tissues. Our results show similar clustering performance compared to that when using real scRNA-seq datasets [29].…”
Section: Methodssupporting
confidence: 68%
“…In fact, the transcriptome can help decipher the true configuration of the inner network of cancer cells much more than the simple knowledge of mutated genes; by observing the shift in gene expression, the true weight of each mutation can be inferred. In addition, transcriptomic analysis can identify another class of oncogenic drivers: those that depend not on a DNA mutation (and are, therefore, invisible to genomic profiling) but only on under-or overexpression [123].…”
Section: Discussionmentioning
confidence: 99%
“…The second group of studies implemented GNNs to predict lncRNA–disease associations [ 35 , 36 , 38 , 39 , 40 , 41 , 46 , 47 , 50 ]. These studies demonstrated superior performance in making predictions, and were able to handle multi-view data and efficiently fuse node features, topological structures, and semantic information.…”
Section: Deep Learning Approaches In the Prediction Of Lncrna–disease...mentioning
confidence: 99%